Allele-Dependent Barley Grain β-Amylase Activity - Erkkilä, Maria J. (American Society of Plant Physiologists, 1998)
The wild ancestor of cultivated barley, Hordeum vulgare subsp. spontaneum (K. Koch) A. & Gr. (H. spontaneum), is a source of wide genetic diversity, including traits that are important for malting quality. A high β-amylase trait was previously identified in H. spontaneum strains from Israel, and transferred into the backcross progeny of a cross with the domesticated barley cv Adorra. We have used Southern-blot analysis and β-amy1 gene characterization to demonstrate that the high β-amylase trait in the backcross line is co-inherited with the β-amy1 gene from the H. spontaneum parent. We have analyzed the β-amy1 gene organization in various domesticated and wild-type barley strains and identified three distinct β-amy1 alleles. Two of these β-amy1 alleles were present in modern barley, one of which was specifically found in good malting barley cultivars. The third allele, linked with high grain β-amylase activity, was found only in a H. spontaneum strain from the Judean foothills in Israel. The sequences of three isolated β-amy1 alleles are compared. The involvement of specific intron III sequences, in particular a 126-bp palindromic insertion, in the allele-dependent expression of β-amylase activity in barley grain is proposed.